A relação entre liderança responsável e os comportamentos individuais no trabalho: o papel do compromisso afetivo - Simões, L. M. (2020)
In recent years, there have been scandals in the organizational world, triggered by ethical lapses, which discredit organizations, namely, in the way they operate in the market and the type of leaders they have, which has created tension in the relationship withand trust of their stakeholders (Voegtlin et al., 2012; Waldman & Siegel, 2008). In response to this problem, a new type of leadership has been proposed, which allows responding to the challenges that organizations are facing - responsible leadership. This study aims to analyze the relationship between responsible leadership and individual behaviors at work, specifically individual performance and organizational citizenship behaviors, as well as whether employees' affective commitment to the organization mediates the previous relationship. To empirically analyze the research model, a quantitative correlational approach was used. The data were collected through an online questionnaire. 298 employees from different organizations operating in Portugal responded, voluntarily and anonymously, to the questionnaire. The data were analyzed using the PROCESS macro software for IBM SPSS 26. The results indicated the existence of a significant relationship between employees' perceptions of responsible leadership and their individual work behaviors. Furthermore, affective commitment significantly mediates the relationship between responsible leadership and individual work behaviors, specifically individual performance and organizational citizenship behaviors. This study reinforces the idea that organizations can increase their employees' affective commitment and, consequently, increase their individual performance and organizational citizenship behaviors by promoting the adoption of responsible leadership behaviors by their leaders.